Profit Maximization Strategies Employed by the Small and Medium Size Building Contractors in Dar-Es-Salaam, Tanzania - Elizabeth H. Kyssima; Dennis N.G.A.K. Tesha; Didas S. Lello; Flaviana S. Mtitu (International Journal of Engineering and Management Research, 2020)
When it comes to a firm’s growth, profitability and profit maximization are sensitive matters that cannot be neglected, due to the fact that profit and profit maximization are the main aims for any building construction business. Thus, the study intended to explore the profit maximization opportunities available for small and medium size building contractors (SMSBCs) in Dar-Es-Salaam, Tanzania; by exploring the profit maximization strategies employed; examining the challenges faced by these contractors that affect realization of profit maximization; and proposing profit maximization measures, that can be employed by the SMSBCs in Dar-Es-Salaam, Tanzania. This designed survey study, employed the SMSBCs in Dar-Es-Salaam Tanzania, as a unit of analysis, which involved building contractors from Class IV, V, VI and VII, as study population and unit sample. Moreover, the descriptive design survey study involved probability sampling as a sampling technique. Literature review; open and closed ended questionnaires, were used in collecting primary and secondary qualitative and quantitative data. In collecting data, total of 94 questionnaires were distributed, whereby 78 (84.3%) were returned. Quantitative data were analyzed using Statistical Package for Social Sciences (SPSS), while qualitative data were analyzed thematically. Findings revealed charging for all amendments and change orders; dropping of low performers; minimization of waste on site; timely execution of works on site; proper tendering procedures; improving construction productivity; reliable chain of supplies; and requiring more site job experience, as the most important opportunities employed by SMSBCs. Furthermore, the critical challenges revealed were; non-payment of debts; taxes and license; lack of capital equipment; low share of work opportunities; delays caused by clients; as well as uncertainty and unexpected climate conditions. The study concluded that; most of the contractors use all the opportunities to maximize their profits in construction projects. Most of them have survived because, they continued maintaining professionalism when it comes to work despite having low share of work/ tender opportunities. Also, corruption is one of the critical factors that affects the industry, hence hindering the contractor’s growth. With the new reform and government systems, this factor has reduced to some extent as compared to how businesses were operated before, but not completely eliminated. The overall satisfaction of the profits and growth of these SMSBCs has been reduced by government reforms and policies, despite the government effort to fight corruption. When it comes to taxes and license fees, most of the contractors are irritated with constant need to pay for cost/license of operations or the presence of both withholding tax and Skills Development Levy(SDL) imposed to them when conducting business. Lastly, the study recommended; introduction of proper taxation policies; centralization of government agencies responsible for collecting annual payment from contractors should be centralized, in which only one agency should be used to supervise process; payment made by government for its construction projects to be made on time; as well as government making sure on the availability of equal opportunities for tenders in private and public sector.